THE ROLE OF AI IN THE DEVELOPMENT OF MSMES IN INDONESIA AND ITS RELEVANCE TO THE CONCEPT OF MAQĀṢID ASH-SHARĪʿAH - Hafidz Zainul Mustofa; Khusniati Rofiah; Azme bin Haji Matali (Universitas Airlangga, 2026)
Artificial Intelligence (AI) has the potential to drive economic growth and inclusion, but its use faces ethical and social challenges. Meanwhile, MSMEs, as pillars of the economy, need to adapt to digitalization to increase competitiveness. The Making Indonesia 4.0 program and e-commerce accelerate this transformation, with AI playing a role in business efficiency. In Islamic economics, Maqāṣid ash-Sharīʿah can guide the use of AI technology to remain oriented towards social welfare and sustainability. However, the relevance of AI for MSMEs within the Maqāṣid ash-Sharīʿah framework remains underexplored. This study aims to: (1) analyze the role of AI in the development of MSMEs in Indonesia; and (2) evaluate its alignment with the principles of Maqāṣid ash-Sharīʿah in promoting ethical and sustainable economic outcomes. This study employed a qualitative method using a Systematic Literature Review (SLR) of Scopus-indexed publications from 2021 to 2024. Data were obtained from the Scopus database and supplemented with supporting literature, and analyzed using thematic coding techniques. This study found that AI enhances MSME efficiency, competitiveness, service quality, financial accuracy, market expansion, innovation, well-being, and alignment with ethical and halal systems. Although resource constraints persist, government initiatives increasingly support digitalization and AI adoption. From a Maqāṣid perspective, AI also aligns with justice and social welfare. This study contributes to the literature by integrating AI with Maqāṣid ash-Sharīʿah in the context of MSME development, an underexplored area. The findings suggest the need for policy support to facilitate AI adoption while ensuring alignment with Islamic ethical principles.